Using Digital Documents and Materials in Civil and Arbitration Procedures - M. Golovanov, Nikolay; ., . (International Journal of Engineering and Technology, 2018)
The research topicality is due to the broad use of digital documents and materials in civil circulation, and the imperfection of the existing legislation in determining their legal status. This situation negatively influences the evidential significance of the digital documents and materials when presented in civil and arbitration procedures.The article objective is to reveal the lacunas in the legal regulation of digital documents and materials as evidences when investigating disputes in general and arbitration courts, and to elaborate proposals for their elimination.The key approach to the research was the legal analysis of legislative and departmental normative legal acts mentioning digital documents, and the analysis of special literature in this sphere of social relations.The main results of the research are: formulating the definition of a digital document setting its most general features and enabling to establish this definition as a legal one; setting the criteria for distinguishing a digital document and a digital material, an original and a copy of a digital document; defining digital documents and materials as direct or indirect evidences, depending on their evidential significance.The conclusions presented in the article can be used by legislators when correcting the norms of the Civil Procedural Code of the Russian Federation (CPC RF) and Arbitration Procedural Code of the Russian Federation (APC RF), other special laws, and by judicial agencies when administering justice on civil cases.Â Â